Boldine improves endothelial function in diabetic db/db mice through inhibition of angiotensin II mediated BMP4 oxidative stress cascade - Lau, Y.S.; Tian, X.Y.; Mustafa, Mohd Rais; Murugan, D.; Liu, J.; Zhang, Y.; Lau, C.W.; Huang, Y. (Nature Publishing Group, 2013)
BACKGROUND AND PURPOSE: Boldine is a potent natural antioxidant present in the leaves and bark of the Chilean boldo tree. Here we assessed the protective effects of boldine on endothelium in a range of models of diabetes, ex vivo and in vitro. EXPERIMENTAL APPROACH: Vascular reactivity was studied in mouse aortas from db/db diabetic and normal mice. Reactive oxygen species (ROS) production, angiotensin AT1 receptor localization and protein expression of oxidative stress markers in the vascular wall were evaluated by dihydroethidium fluorescence, lucigenin enhanced-chemiluminescence, immunohistochemistry and Western blot respectively. Primary cultures of mouse aortic endothelial cells, exposed to high concentrations of glucose (30 mmol L(-1) ) were also used. KEY RESULTS: Oral treatment (20 mg kg(-1) day(-1) , 7 days) or incubation in vitro with boldine (1 Î¼mol L(-1) , 12 h) enhanced endothelium-dependent aortic relaxations of db/db mice. Boldine reversed impaired relaxations induced by high glucose or angiotensin II (Ang II) in non-diabetic mouse aortas while it reduced the overproduction of ROS and increased phosphorylation of eNOS in db/db mouse aortas. Elevated expression of oxidative stress markers (bone morphogenic protein 4 (BMP4), nitrotyrosine and AT1 receptors) were reduced in boldine-treated db/db mouse aortas. Ang II-stimulated BMP4 expression was inhibited by boldine, tempol, noggin or losartan. Boldine inhibited high glucose-stimulated ROS production and restored the decreased phosphorylation of eNOS in mouse aortic endothelial cells in culture. CONCLUSIONS AND IMPLICATIONS: Boldine reduced oxidative stress and improved endothelium-dependent relaxation in aortas of diabetic mice largely through inhibiting ROS overproduction associated with Ang II-mediated BMP4-dependent mechanisms.